The Development of the Concept of Fair Value - O. V. Rozhnova (Учёт. Анализ. Аудит, 2019)
The article considers the issues of the content and the development of the concept of fair value. This concept has acquired the modern shape during the last two decades. Currently it is used in the International Financial Reporting Standards (IFRS) along with the concept of valuation at historical cost. The article examines the differences between these two concepts, as well as the models in which these concepts are applied directly in the financial reporting standards. The comparison is carried out according to eleven aspects: the possibility of using; its recognition in the statement of profit or loss/other comprehensive income of negative and positive changes in fair value; depreciation; the influence of fair value on the traditional indicators according to which the effectiveness of the company is assessed; risks inherent to the indicators obtained on the basis of the model; the use of valuation at fair value; permitting analytical capabilities; the complexity of determining the appraisal values. The article shows the advantages of the concept of fair value, its “coincidence” with the market economy and the role in its transformation and also the movement towards the new horizons. It is also noted in the article about the great importance of this concept for management accounting, and as a result, the potential possibility to use the principle of rationality when it is applied for the formation of financial reporting, i.e. it is noted that the advantages of the concept of fair value are greater compared to the costs of value determination of the fair value of the accounting entities. The concept of fair value allows to make the financial reporting more useful for the users, although it requires the socalled reinstallation of the analysis of financial condition and the results of the operations of the economic entities in accordance with the new indicators, methods and factors related to the assessment at fair value. The article proposes within the concept of fair value a combined model of fair value and substantiates the positive results of its application when reflecting the fixed assets in the financial statements of the economic entities. In conclusion, the article gives the following directions for further research regarding the concept of fair value, including the search for its new incarnations as well as the objects of its study.